Consumption and wealth in Luke's travel narrative - Metzger, James A. (Biblical Interpretation Series, 2007)
It is suggested that because persons with access to a large surplus too often elect to spend extravagantly on their own desires and existing means of redistribution such as almsgiving and beneficence were failing to offer any lasting changes that might truly be received as \'good news\' by the poor, Jesus advocates eliminating personal wealth.